Tokoh Cerita dalam Antologi "Tangan-Tangan Mungil Melukis Langit" - Rini Widiastuti (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This research aimed at to know the character in “Tangan-Tangan Mungil Melukis Langit” anthlology is viewed from children psychology used qualitative descriptive method and library research technique.The analysis result describing the characters in “Tangan-Tangan Mungil Melukis Langit” anthology are about the scary Faiz could change the scared, the loving Caca seek the way to delight her sister,Cici and Lili, her intrepid rabbit who infiltrate the cat kingdom bravely, the generous Rafifah gives her hard-earned money proudly, Character Dirti is spoiled, dependent, cranky, bossy and annoying, andalso the helpful Aidan is defender of the weak got the power when the blue light against him.